Enhanced anaerobic biodegradation of 17α-ethinylestradiol via a flow-through electrode - Jiale Zheng; Zhen Lei; Yuan Yang; Mei Chen; Rong Chen (Bioresource Technology, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Uncovering the effect of drying process on aquaporin proteins and fruit quality of goji berry (Lycium barbarum), a worldwide popular functional food - Zhigang Li; Rong Jiang; Zhiqiang Wang; Juanjuan Mi; Juanhong Zhao; Zhanfei Liu; Yuan Liu; Guoqi Zheng; Shaohua Zeng (Food Chemistry, 2026)

Quantifying the light interception and canopy photosynthesis of strip intercropping system based on 3D canopy photosynthesis model - Si-Rong Huang; Qing-Feng Song; Zheng Guo; Qiu-Feng Long; Li-Sha Zhang; Yue Li; Yuan Yang; Xiao-Chun Wang; Feng Yang; Tai-Wen Yong; Jiang Liu; Yan-Hong Yan; et al. (Computers and Electronics in Agriculture, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Current warming exceeds medieval warm period in impact on Tibetan Plateau lake ecosystems - Jianan Zheng; Rong Wang; Yu Zhao; Kexin Zhu; Yanjie Zhao; Yuan Li; Ke Zhang; Hao Long; Ji Shen (Quaternary Science Reviews, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Chemical constituents and ferroptosis inhibitory activity of the deep-sea-derived fungus Penicillium citrinum W24 - Cheng-You Lin; Yuan Wang; Tai-Zong Wu; Rong Chao; Zheng-Biao Zou; Li-Sheng Li; Tian-Hua Zhong; Xian-Wen Yang (Natural Product Research, 2026)

A germline-specific vesicular structure licenses mRNA activation during spermiogenesis and is hijacked in gastric cancer - Mingxi Liu; Zerui Wang; Yinuo Li; Qingsong Xie; Zhuang Xiao; Xuezhi He; Guanxiong Wang; Yang Gao; Yini Zhang; Lin Zheng; Xun Xia; Lujie Chen; et al. (Science Bulletin, 2026)

Metabolic reprogramming by baicalein disrupts fibroblast–macrophage crosstalk in idiopathic pulmonary fibrosis - Wen Zhang; Liu-Liu Yuan; Jia-Rong Li; Tian-Sheng Zheng; Li-Hong Fan (Chemico-Biological Interactions, 2026)

Corrigendum to “Flooding duration affects the temperature sensitivity of soil extracellular enzyme activities in a lakeshore wetland in Poyang Lake, China” [Sci. Total. Environ., Volume 874 (2023), 162397] - Xingyun Huang; Kexin Wang; Xiuting Wen; Jie Liu; Yan Zhang; Jun Rong; Ming Nie; Chun Fu; Bofu Zheng; Zhifen Yuan; Ruichang Shen (Science of The Total Environment, 2026)

RBOHC-derived ROS control plant nitrate starvation response via WRKYs-activated expression of high-affinity nitrate transporters - Tian Yuan; Meng-Qi Cui; Chen Xu; Jing-Ying Yan; Wo-Na Ding; Ji-Ming Xu; Yun-Rong Wu; Gui-Xin Li; Yu Liu; Dong Zhang; Chuan-Zao Mao; Moussa Benhamed; et al. (Science Bulletin, 2026)

Experimental evidence on the bitumen role of the metal enrichment in the Erdaokan Ag-Pb-Zn deposit - Shun-Feng Yan; Xiao-Min Zheng; Lin Li; Hai-Yan Zheng; Mao-Wen Yuan; M. Santosh; Sheng-Rong Li (Organic Geochemistry, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

The low R = d/d high-entropy strategy enables high-performance sodium layered oxide cathode materials - Jun-Jie Liao; Min Wen; Wei-Wei Yuan; Qi-Lin Zheng; Kang Chen; Fu-Sheng Zhou; Zhen-Xin Qiu; Su-Yun Wang; Li-Li Wang; Lituo Zheng; Yiyin Huang; Jia-Xin Li; et al. (Chemical Engineering Journal, 2026)

Shared E-bikes are more resilient than shared bikes to extreme temperatures: Evidence from Citi Bike in New York City - Rong Zheng; Yuan Liang; Donggen Wang; Yifu Ou (Journal of Transport Geography, 2025)

The multimodal anti-tumor effect of cisplatin nanoparticles loaded with bacterial antibodies in combination with radiotherapy: targeting hypoxic tumor and reshaping of the immune microenvironment - Min Wu; Zhouxue Wu; Weizhou Wang; Yunxue Zheng; Hongxia Li; Yuan Huang; Liping Deng; Yingqi Gu; Jinfeng Rong; Xiaoyin Zhang; Wen Yang; Yue Chen; et al. (Chemical Engineering Journal, 2025)

Synergistic Cr(VI)/Oxytetracycline co-removal via acid-stable non-radical pathways enabled by plasmonic Z-scheme W18O49/Bi4NbO8Cl heterojunction - Chu-Jia Jin; Huai-Yuan Niu; Lei Ma; Ya-Ya Yang; Long Sui; Zheng-Tao Dong; Yan-Rong Peng; Ming Yan; Cheng-Gang Niu (Chemical Engineering Journal, 2025)

R-P phase high-entropy perovskite La0.5Sr1.5Mn0.2Fe0.2Ni0.2Cu0.2Co0.2O4 achieves complete PMS utilization via multi-pathway activation for efficient water purification - Lei Ma; Huai-Yuan Niu; Chu-Jia Jin; Long Sui; Zheng-Tao Dong; Yan-Rong Peng; Ming Yan; Cheng-Gang Niu (Chemical Engineering Journal, 2025)

Phthalocyanine-based nanosensitizers for enhanced sonodynamic therapy activity of hypoxic tumor with dual apoptosis/ferroptosis pathways - Xue-Yan Li; Jin Liu; Bi-Yuan Zheng; Mei-Rong Ke; Jian-Dong Huang (Journal of Photochemistry and Photobiology B: Biology, 2025)

Unraveling the effect of sorbitol on Cu-based catalysts for the continuous hydrogenation of CO2-derived ethylene carbonate to methanol and ethylene glycol - Tong-Yang Song; Ji-Zheng Zhang; Jun He; Xian-Lang Chen; Xin-Yuan Huang; Ai-Ping Jia; Xiaohong Li; Rong-Rong Li; Ji-Qing Lu (Chemical Engineering Journal, 2025)

A leapfrog improvement in N-butanol detection achieved through single atom catalysts Co-N-C - Luhan Cheng; Zhixiang Yuan; Rong Wu; Zhou Li; Jun Zheng; Jiming Song (Chemical Engineering Journal, 2025)

Front margin tectonic deformation characteristics of the Xu–Su arc tectonic belt and its tectonic implications - Rong-ying Zheng; Yun-sheng Yao; Jun Shen; Hao-yuan He; Chun-shan Guo; Xiao-hui Yu; Xun-ye Dai; Lu-wei Li; Xuan-kai Jiao; Zhong-yuan Yu; Zhi-tao Gao (Applied Geophysics, 2025)

An end-to-end maturity prediction and hierarchical counting method for cherry tomatoes - Jiacheng Rong; Xianjun Li; Wanli Zheng; Tongqiang Chen; Ting Yuan; Pengbo Wang; Wei Li (Biosystems Engineering, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Low-valent Cu doping optimizes Ruddlesden-Popper perovskite for accelerated levofloxacin removal: Enhanced Ni-dominated dual radical/nonradical pathways - Lei Ma; Chu-Jia Jin; Huai-Yuan Niu; Zheng-Tao Dong; Long Sui; Qian Wu; Yan-Rong Peng; Jia-jia Wang; Cheng-Gang Niu (Journal of Hazardous Materials, 2025)

Chemical constituents of the deep-sea-derived fungus Purpureocillium lilacinum XIA-18 and their chemotaxonomic significance - Bao-Fu Li; Yuan Wang; Zheng-Biao Zou; Rong Chao; Tai-Zong Wu; Ying-Ni Pan; Xian-Wen Yang (Biochemical Systematics and Ecology, 2025)

Ultrastructure and sense organs of ovipositors in the phytophagous gall-maker pest Ophelimus maskelli (Hymenoptera: Eulophidae) and its parasitoid, Closterocerus chamaeleon (Hymenoptera: Eulophidae) - Yuan-Hao Li; Yu-Yue Huang; Yu-Chun Huang; Xiao-Rong Tang; Wen-Ting Huang; Xia-Lin Zheng (Journal of Asia-Pacific Entomology, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

The promotional effect of MoO3 on the CeO2/TiO2 catalyst for simultaneous removal of NO and toluene: From the insights of experimental and DFT studies - Zhuang Hu; Yi-fei Yu; Hai-yuan Zhao; Zheng-long Wu; Rong Guo; Jia-le Zhou; Xin-yue Zhou; Bing Zhang; Yang-wen Wu; Li Zhao; Qiang Lu (Journal of Environmental Chemical Engineering, 2025)

Interfacial structure design enables rapid reaction kinetics for high-voltage NCM 613 cathodes - Yuan Xiao; Rong Gu; Tingting Zheng; Bowen Chang; Qiaoxia Li; Shuaiqi Gong; Xin Wei; Qunjie Xu; Yulin Min (Chemical Engineering Journal, 2025)

Design, synthesis, biological evaluation, and in silico studies of imidazo[2,1-b][1,3,4]thiadiazole derivatives as cholinesterase inhibitors - Wen-Rong Du; Yi-Xuan Wang; Xue-Wei Zhou; Yong Lan; Ben-Ben Wei; Xin-Yuan Guo; Xiao-Ke Wang; Zheng-Yue Ma (Medicinal Chemistry Research, 2025)

Late Quaternary slip rate of the Northern Margin Fault of the Huaizhuo Basin in the North China Block and its seismological implications - Lu-wei Li; Zhong-yuan Yu; Chun-miao Qiu; Wen-xuan Wang; Qian Zhao; Rong-ying Zheng; Yan-Lin Yang (Applied Geophysics, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Enhancing the photo-induced oxidase-like activity of fluorescein with methyl viologen for colorimetric detection of organophosphorus pesticide - Yang Yin; Caiyun Yuan; Xinyu Wang; Dongjun Shen; Yu Rong; Jijun Liu; Yijuan Long; Huzhi Zheng (Food Chemistry, 2025)

A tumor-pH-responsive phthalocyanine as activatable type I photosensitizer for improved photodynamic immunotherapy - Ling Zhang; Rong-Bin Que; Ting-Ting Ke; Chao Wang; Wei Xie; Hong-Jie Sun; Bi-Yuan Zheng; Mei-Rong Ke; Jian-Dong Huang; Xingshu Li (Journal of Photochemistry and Photobiology B: Biology, 2024)

Cohort Profile: TRacing Etiology of Non-communicable Diseases (TREND): Rationale, Progress and Perspective - Hui-Ying Ren; Ying Lv; Bei-Ning Ma; Chang Gao; Hong-Mei Yuan; Hai-Hong Meng; Zheng-Qian Cao; Ya-Ting Chen; Yan-Xi Zhang; Yu-Ting Zhang; Wei Liu; Yu-Ping Fan; et al. (Phenomics, 2024)
The TRacing Etiology of Non-communicable Diseases (TREND) cohort is a prospective longitudinal cohort and biobank that is mainly based in Ma’anshan, Anhui Province, China. The primary aim of the study is to decipher comprehensive molecular characterization and deep phenotyping for a broad spectrum of chronic non-communicable diseases (NCDs), which focuses on providing mechanistic insights with diagnostic, prognostic and therapeutic implications. The recruitment was initiated in 2023 and is expected to complete in 2025 with 20,000 participants originated from urban and rural area. In the first phase, 3360 participants were recruited. Follow-up visits are scheduled annually and intervally for a total of 30 years. The cohort includes individuals aged over 18 years. Two participants with first-degree linkage were recruited from a household. The age distribution of recruited participants was stratified into four categories: 18–45, 45–55, 55–65, and ≥65 years, aligning with the population proportions of Ma’anshan. Meanwhile, the gender distribution was controlled by pairing men and women from the same household. Data collected at baseline includes socio-economic information, medical history, lifestyle and nutritional habits, anthropometrics, blood oxygen, electrocardiogram (ECG), heart sound, as well as blood, urine and feces tests results. Molecular profiling includes genome, proteome, metabolome, microbiome and extracellular vesicles -omics. Blood, urine and fecal samples are collected and stored at −80 °C in a storage facility for future research.

Active tectonic deformation and its seismic–geological significance of boundary faults of the Daxing Uplift and Langgu–Dachang Depression, Beijing Plain, China - Rong-Ying Zheng; Zhong-Yuan Yu; Bai-Xu Chen; Lu-Wei Li; Yi-Cheng Wang (Applied Geophysics, 2024)

Noradrenergic Projections from the Locus Coeruleus to the Medial Prefrontal Cortex Enhances Stress Coping Behavior in Mice Following Long-Term Intermittent Fasting - Zheng Zhao; Jun-Liang Chen; Han Zhan; Chang-Rong Fang; Li-Bo Hua; Hao-Yuan Deng; Zongqin Xiang; Ying Yang; Lang Huang; Yong U. Liu (NeuroMolecular Medicine, 2024)

The nexus between technological innovation capabilities and carbon mitigation in firms: moderating roles of external and internal innovation pathways - Nan Li; Rong Yuan; Shenglin Zheng (Environment, Development and Sustainability, 2024)

Synergic treatment of domestic wastewater and food waste in an anaerobic membrane bioreactor demo plant: Process performance, energy consumption, and greenhouse gas emissions - Zhen Lei; Jiale Zheng; Jiale Liu; Qian Li; Jingjing Xue; Yuan Yang; Zhe Kong; Yu-You Li; Rong Chen (Water Research, 2024)

Fabrication of graphene oxide/ammonium molybdophosphate composite membrane for decontamination of cesium ions from seawater - Xiao-Yi Tang; Zi-Jie Li; Lin Wang; Peng-Cheng Zhang; Kong-Qiu Hu; Li-Rong Zheng; Zhi-Hui Zhang; Li-Yong Yuan; Wang-Suo Wu; Wei-Qun Shi (Chemical Engineering Journal, 2024)

Design, synthesis and evaluation of imidazo[1,2-a]pyrazin-8(7H)-one derivatives as acetylcholinesterase inhibitors and antioxidants - Wen-Rong Du; Ben-Ben Wei; Xin-Yuan Guo; Yong Lan; Pan-Pan Shang; Yi-Xuan Wang; Xue-Wei Zhou; Xiao-Ke Wang; Zheng-Yue Ma (Medicinal Chemistry Research, 2024)

Phthalocyanine J-aggregate nanoparticles with enormous-redshifted and intense absorption: Potential structure-J-aggregation relationships and application in tumor-associated macrophages-targeted phototheranostics - Fengxiang Tang; Haodong Yu; Yanzong Huang; Xue Zhao; Zixuan Chen; Honglin Ma; Bi-Yuan Zheng; Mei-Rong Ke; Yongfan Zhang; Xingshu Li; Juyoung Yoon; Jian-Dong Huang (Chemical Engineering Journal, 2024)

MR Molecular Image Guided Treatment of Pancreatic Cancer with Targeted ECO/miR-200c Nanoparticles in Immunocompetent Mouse Tumor Models - Victoria Laney; Ryan Hall; Xueer Yuan; Emma Hampson; Augusta Halle; Grace Yeung; Kristen-Weber Bonk; Suneel Apte; Jordan Winter; Ruth Keri; Zheng-Rong Lu (Pharmaceutical Research, 2024)
Objective Pancreatic ductal adenocarcinoma (PDAC) is characterized by desmoplasia due to increased deposition of extracellular matrix (ECM) proteins. This work investigates the efficacy of targeted ECO/miR-200c nanoparticles (ELNP) on ECM remodeling in PDAC and tumor proliferation with MR molecular imaging (MRMI) with MT218 in immunocompetent mouse models. Methods The miR-200c mediated regulation of EMT markers was measured in PDAC cells in vitro . Wild-type mice bearing mutated KRAS-driven KPC subcutaneous or orthotopic tumors were dosed weekly with RGD-ELNP/miR-200c at 1 mg-RNA/kg for a total of 4 doses. We utilized MT218-MRMI to non-invasively monitor the alteration of tumor ECM EDN-FN levels by miR-200c and tumor response to the treatment. The changes were also validated by posthumous histopathology. Results Transfection of PDAC cells with ELNP/miR-200c downregulated the expression of FN1 and EDB-FN and some mesenchymal markers, inhibiting 3D spheroid formation and migration of KPC PDAC cells. RGD-ELNP/miR-200c treatment resulted in significant signal reduction in the MT218 enhanced MRMI images of both subcutaneous and orthotopic KPC tumors compared to those prior to treatment and treated with a non-specific control. MT218-MRMI results were suggestive of EDB-FN downregulation in tumors, which was later confirmed by immunohistochemistry. Tumor growth in subcutaneous tumors was significantly attenuated with RGD-ELNP/miR-200c and was an observed trend in orthotopic tumors. Substantial necrosis and remodeling were observed in both models treated with RGD-ELNP/miR-200c based on H&E staining. Conclusion These results demonstrate the feasibility of RGD-ELNP/miR-200c in modulating PDAC ECM and restraining tumor growth and the utility of MT218-MRMI for non-invasively monitoring miR-200c efficacy.

SAD2 functions in plant pathogen Pseudomonas syringae pv tomato DC3000 defense by regulating the nuclear accumulation of MYB30 in Arabidopsis thaliana - Tiantian Shi; Yuan Zheng; Rui Wang; Sha Li; Andi Xu; Luoying Chen; Yuanhang Liu; Rong Luo; Chenchen Huang; Yinglu Sun; Jinfeng Zhao; Xiaoying Guo; et al. (Plant Science, 2024)

Effects of internal waves on bottom thermal structures and turbulent mixing in the Xisha Islands - Ming-Quan Zhu; Xian-Rong Cen; Sheng-Qi Zhou; Yuan-Zheng Lu; Shuang-Xi Guo; Peng-Qi Huang; Ling Qu (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

Exploring near-bottom turbulent mixing across the Challenger Deep based on temperature spectral analysis - Yuan-Zheng Lu; Shuang-Xi Guo; Sheng-Qi Zhou; Peng-Qi Huang; Jian Lin; Xian-Rong Cen; Ling Qu (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

Boosting persulfate activation through efficient π → π* transition activated by Cu ion anchored porphyrin-based metal–organic framework - Wen-Qiang Li; Oleksandr Savateev; Yuan-Ming Li; Jian-Kang Zheng; Yi-Xuan Wang; Nannan Hou; Xiao-Cheng Liu; Rong-Rong Ding; Xiao-Guo Zhou; Yang Wang; Xian-Yang Shi; Yang Mu (Chemical Engineering Journal, 2024)

Chemical constituents of the deep-sea-derived fungus Trichoderma simmonsii ZEN3 and their chemotaxonomic significance - Li-Fang Liu; Yuan Wang; Rong Chao; Lin Xu; Zheng-Biao Zou; Kai Zhang; Ming-Min Xie; Xian-Qiang Chen; Cheng-Hai Gao; Xian-Wen Yang (Biochemical Systematics and Ecology, 2024)

Graphene oxide quantum dots (GOQDs) induce behavioral disorders via the disturbance of kynurenine pathway in zebrafish larvae - Shun Deng; Enming Zhang; Yunyang Zhao; Hao Guo; Lan Luo; Song Yi; Bingxin Zheng; Xiaoyuan Mu; Kezhu Yuan; Xuangen Deng; Haibo Rong; Yanbo Ma; et al. (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

A multi-species pest recognition and counting method based on a density map in the greenhouse - Zhiqin Zhang; Jiacheng Rong; Zhongxian Qi; Yan Yang; Xiajun Zheng; Jin Gao; Wei Li; Ting Yuan (Computers and Electronics in Agriculture, 2024)

Anthropogenic disturbance driving population decline of a dominant tree in East Asia evergreen broadleaved forests over the last 11,000 years - Sheng‐Yuan Qin; Zheng‐Yu Zuo; Shuang‐Xiu Xu; Jie Liu; Feng‐Mao Yang; Ya‐Huang Luo; Jun‐Wei Ye; Yao Zhao; Jun Rong; Bing Liu; Peng‐Fei Ma; De‐Zhu Li (Conservation Biology, 2024)
Current biodiversity loss is generally considered to have been caused by anthropogenic disturbance, but it is unclear when anthropogenic activities began to affect biodiversity loss. One hypothesis suggests it began with the Industrial Revolution, whereas others propose that anthropogenic disturbance has been associated with biodiversity decline since the early Holocene. To test these hypotheses, we examined the unique vegetation of evergreen broadleaved forests (EBLFs) in East Asia, where humans have affected landscapes since the early Holocene. We adopted a genomic approach to infer the demographic history of a dominant tree ( Litsea elongata ) of EBLFs. We used Holocene temperature and anthropogenic disturbance factors to calculate the correlation between these variables and the historical effective population size of L. elongata with Spearman statistics and integrated the maximum‐entropy niche model to determine the impact of climate change and anthropogenic disturbance on fluctuation in its effective population size. We identified 9 well‐defined geographic clades for the populations of L. elongata . Based on the estimated historical population sizes of these clades, all the populations contracted, indicating persistent population decline over the last 11,000 years. Demographic history of L . elongata and human population change, change in cropland use, and change in irrigated rice area were significantly negatively correlated, whereas climate change in the Holocene was not correlated with demographic history. Our results support the early human impact hypothesis and provide comprehensive evidence that early anthropogenic disturbance may contribute to the current biodiversity crisis in East Asia.

Associations of legacy perfluoroalkyl and polyfluoroalkyl substances, alternatives, and isomers with gestational diabetes mellitus and glucose homeostasis among women conceiving through assisted reproduction in Shanghai, China - Dandan Mao; Guodong Ding; Zixia Wang; Jiuru Zhao; Hong Li; Xiaoning Lei; Jiaqi Zheng; Yan Zhang; Rong Shi; Tao Yuan; Zhiwei Liu; Yu Gao; et al. (Environmental Science and Pollution Research, 2024)

Will technological factors promote the decoupling of emissions? A cross-sectoral analysis of Chinese industrial listed firms - Nan Li; Rong Yuan; Shenglin Zheng (Environmental Impact Assessment Review, 2024)

Occurrence of liquid crystal monomers in indoor and outdoor air particle matters (PM10): Implications for human exposure indoors - Li-Li Yao; Jun-Li Wang; Rong-Fa Xu; Ming Zhu; Yan Ma; Bin Tang; Qi-Yuan Lu; Feng-Shan Cai; Xiao Yan; Jing Zheng; Yun-Jiang Yu (Science of The Total Environment, 2023)

Screening of small molecule compounds targeting hnRNPA2 protein - Yuan-Rong Zheng; Chao-Jie Wang; Ling Yang; Yu-Jun Zhang; Mei-Juan Fang; He Chang; Kai-Qiang Guo; Song-Lin Shi (Medicinal Chemistry Research, 2023)

Impacts of interprovincial migration on the household energy footprints in China - Rong Yuan; Nan Li; Shenglin Zheng (Applied Geography, 2023)

Flooding dominates soil microbial carbon and phosphorus limitations in Poyang Lake wetland, China - Xingyun Huang; Yaxuan Li; Huiyin Lin; Xiuting Wen; Jie Liu; Zhifen Yuan; Chun Fu; Bofu Zheng; Leiqiang Gong; Huiying Zhan; Yu Ni; Yang Hu; et al. (CATENA, 2023)

Three new hasubanan-type alkaloids from the Stephania longa - Rong-Xiao Lin; Lixia Fan; Xin Chen; Jundi Wu; Zheng Liu; Fang Liu; An-Ping Yang; Chenglai Xia; Hui Liu; Hong-Yuan Chen (Natural Product Research, 2023)

Experimental investigation of the seismic resistance of RC beam–column connections after freeze–thaw cycle treatment - Xian-Liang Rong; Lei Li; Wei-Yuan Huang; Li-Guo Dong; Shan-Suo Zheng; Feng Wang; Dong Lu; Jun-Yan Wang (Engineering Structures, 2023)

Enhancing fengycin production in the co-culture of Bacillus subtilis and Corynebacterium glutamicum by engineering proline transporter - Geng-Rong Gao; Si-Yu Wei; Ming-Zhu Ding; Zheng-Jie Hou; Dun-Ju Wang; Qiu-Man Xu; Jing-Sheng Cheng; Ying-Jin Yuan (Bioresource Technology, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Corrigendum to “Graphene quantum dots (GQDs) induce thigmotactic effect in zebrafish larvae via modulating key genes and metabolites related to synaptic plasticity” [Toxicology 487 (2023) 1–13] - Shun Deng; Enming Zhang; Junyu Tao; Yunyang Zhao; Wenbo Huo; Hao Guo; Bingxin Zheng; Xiaoyuan Mu; Kezhu Yuan; Xuangen Deng; Hai Shen; Haibo Rong; et al. (Toxicology, 2023)

Impacts of targeted poverty alleviation on urban-rural residential energy consumption inequality: Evidence from 178 Chinese prefecture-level cities - Nan Li; Rong Yuan; Shenglin Zheng (Urban Climate, 2023)

Triterpene constituents from the fruits of Cyclocarya paliurus and their anti-HIV-1 IIIB activity - Wen-Chao Tu; Rong-Hua Luo; En Yuan; Kaunda-Joseph Sakah; Quan-Yu Yang; Wei-Lie Xiao; Yong-Tang Zheng; Mei-Feng Liu (Natural Product Research, 2023)

Phylogenomic insights into the origin and evolutionary history of evergreen broadleaved forests in East Asia under Cenozoic climate change - Sheng‐Yuan Qin; Zheng‐Yu Zuo; Cen Guo; Xin‐Yu Du; Shui‐Yin Liu; Xiang‐Qin Yu; Xiao‐Guo Xiang; Jun Rong; Bing Liu; Zhi‐Fang Liu; Peng‐Fei Ma; De‐Zhu Li (Molecular Ecology, 2023)
The evergreen versus deciduous leaf habit is an important functional trait for adaptation of forest trees and has been hypothesized to be related to the evolutionary processes of the component species under paleoclimatic change, and potentially reflected in the dynamic history of evergreen broadleaved forests (EBLFs) in East Asia. However, knowledge about the shift of evergreen versus deciduous leaf with the impact of paleoclimatic change using genomic data remains rare. Here, we focus on the Litsea complex (Lauraceae), a key lineage with dominant species of EBLFs, to gain insights into how evergreen versus deciduous trait shifted, providing insights into the origin and historical dynamics of EBLFs in East Asia under Cenozoic climate change. We reconstructed a robust phylogeny of the Litsea complex using genome‐wide single‐nucleotide variants (SNVs) with eight clades resolved. Fossil‐calibrated analyses, diversification rate shifts, ancestral habit, ecological niche modelling and climate niche reconstruction were employed to estimate its origin and diversification pattern. Taking into account studies on other plant lineages dominating EBLFs of East Asia, it was revealed that the prototype of EBLFs in East Asia probably emerged in the Early Eocene (55–50 million years ago [Ma]), facilitated by the greenhouse warming. As a response to the cooling and drying climate in the Middle to Late Eocene (48–38 Ma), deciduous habits were evolved in the dominant lineages of the EBLFs in East Asia. Up to the Early Miocene (23 Ma), the prevailing of East Asian monsoon increased the extreme seasonal precipitation and accelerated the emergence of evergreen habits of the dominant lineages, and ultimately shaped the vegetation resembling that of today.

Flooding duration affects the temperature sensitivity of soil extracellular enzyme activities in a lakeshore wetland in Poyang Lake, China - Xingyun Huang; Kexin Wang; Xiuting Wen; Jie Liu; Yan Zhang; Jun Rong; Ming Nie; Chun Fu; Bofu Zheng; Zhifen Yuan; Leiqiang Gong; Huiying Zhan; et al. (Science of The Total Environment, 2023)

An oligosaccharide marker for rapid authentication of edible bird’s nest - Li-Feng Li; Hui-Yuan Cheng; Jun Lang; Tin-Long Wong; Ji-Xia Zhang; Wen-Jie Wu; Quan-Wei Zhang; Hau-Yee Kong; Check-Hei Lai; Hau-Yee Fung; Man Liu; Wan-Rong Bao; et al. (Food Chemistry, 2023)

LncRNA CFAR promotes cardiac fibrosis via the miR-449a-5p/LOXL3/mTOR axis - Mingyu Zhang; Bowen Zhang; Xiaohan Wang; Jiahang Song; Ming Tong; Zheng Dong; Jiaonan Xu; Meng Liu; Yuan Jiang; Ning Wang; Ying Wang; Zhimin Du; et al. (Science China Life Sciences, 2023)

Graphene quantum dots (GQDs) induce thigmotactic effect in zebrafish larvae via modulating key genes and metabolites related to synaptic plasticity - Shun Deng; Enming Zhang; Junyu Tao; Yunyang Zhao; Wenbo Huo; Hao Guo; Bingxin Zheng; Xiaoyuan Mu; Kezhu Yuan; Xuangen Deng; Hai Shen; Haibo Rong; et al. (Toxicology, 2023)

Ancient DNA reveals potentially toxic cyanobacteria increasing with climate change - Jifeng Zhang; Kun Shi; Hans W. Paerl; Kathleen M. Rühland; Yanli Yuan; Rong Wang; Jie Chen; Mengjuan Ge; Lingling Zheng; Zhiping Zhang; Boqiang Qin; Jianbao Liu; et al. (Water Research, 2023)

Cumulative effects of temperature on blood pressure during pregnancy: A cohort study of differing effects in three trimesters - Qi Chen; Ya Wang; Hui-Rong Tang; Yuan Wang; Ai-Hua Gu; Xiang-Jun Zhai; Ming-Ming Zheng (Science of The Total Environment, 2023)

An in silico and in vitro integrated analysis method to reveal the curative mechanisms and pharmacodynamic substances of Bufei granule on chronic obstructive pulmonary disease - Yuan-yuan Ma; Rong Li; Zhi-xian Shang; Wei Liu; Xin-yi Jiao; Liu-yi Liang; Rui Liu; Zheng Li (Molecular Diversity, 2023)

Mutualistic microbial community of Bacillus amyloliquefaciens and recombinant Yarrowia lipolytica co-produced lipopeptides and fatty acids from food waste - Song Bai; Bin Qiao; Zheng-Jie Hou; Geng-Rong Gao; Chun-Yang Cao; Jing-Sheng Cheng; Ying-Jin Yuan (Chemosphere, 2023)

Degradation of antibiotics by electrochemical advanced oxidation processes (EAOPs): Performance, mechanisms, and perspectives - Qingbin Yuan; Siyao Qu; Rong Li; Zheng-Yang Huo; Yan Gao; Yi Luo (Science of The Total Environment, 2023)

Trade-offs between poverty alleviation and household energy intensity in China - Nan Li; Rong Yuan; Shenglin Zheng (Environmental Impact Assessment Review, 2023)

Programmable phthalocyanine-iron-based nanoreactor for fluorescence/magnetic resonance dual-modality imaging-guided sono/chemodynamic therapies - Dong Li; Jie Pan; Shuyu Xu; Bingwei Cheng; Shuaiying Wu; Qixuan Dai; Mei-Rong Ke; Bi-Yuan Zheng; Chengchao Chu; Chao Liu; Yang Zhang; Xiao Xu; et al. (Chemical Engineering Journal, 2023)

Decoupling and scenario analysis of economy-emissions pattern in China’s 30 provinces - Jiayang Chen; Rong Yuan; Shenglin Zheng (Environmental Science and Pollution Research, 2022)

The Predictability of Ocean Environments that Contributed to the 2020/21 Extreme Cold Events in China: 2020/21 La Niña and 2020 Arctic Sea Ice Loss - Fei Zheng; Ji-Ping Liu; Xiang-Hui Fang; Mi-Rong Song; Chao-Yuan Yang; Yuan Yuan; Ke-Xin Li; Ji Wang; Jiang Zhu (Advances in Atmospheric Sciences, 2022)
Several consecutive extreme cold events impacted China during the first half of winter 2020/21, breaking the low-temperature records in many cities. How to make accurate climate predictions of extreme cold events is still an urgent issue. The synergistic effect of the warm Arctic and cold tropical Pacific has been demonstrated to intensify the intrusions of cold air from polar regions into middle-high latitudes, further influencing the cold conditions in China. However, climate models failed to predict these two ocean environments at expected lead times. Most seasonal climate forecasts only predicted the 2020/21 La Niña after the signal had already become apparent and significantly underestimated the observed Arctic sea ice loss in autumn 2020 with a 1–2 month advancement. In this work, the corresponding physical factors that may help improve the accuracy of seasonal climate predictions are further explored. For the 2020/21 La Niña prediction, through sensitivity experiments involving different atmospheric–oceanic initial conditions, the predominant southeasterly wind anomalies over the equatorial Pacific in spring of 2020 are diagnosed to play an irreplaceable role in triggering this cold event. A reasonable inclusion of atmospheric surface winds into the initialization will help the model predict La Niña development from the early spring of 2020. For predicting the Arctic sea ice loss in autumn 2020, an anomalously cyclonic circulation from the central Arctic Ocean predicted by the model, which swept abnormally hot air over Siberia into the Arctic Ocean, is recognized as an important contributor to successfully predicting the minimum Arctic sea ice extent.

Consuming Different Structural Parts of Bamboo Induce Gut Microbiome Changes in Captive Giant Pandas - Zheng Yan; Qin Xu; Walter H. Hsu; Stephan Schmitz Esser; James Ayala; Rong Hou; Ying Yao; Dandan Jiang; Shibin Yuan; Hairui Wang (Current Microbiology, 2021)
Giant pandas consume different structural parts of bamboo (shoots, leaves and culms) during different seasons. Previous research showed different bamboo parts have varying nutritional content and that a long-term diet consisting of a single part of bamboo resulted in remarkable metabolic changes within captive giant pandas. However, the effects on the gut microbiome of giant pandas, as a result of a single bamboo part diet, have not been investigated. Here, we evaluated the changes in gut microbial communities based on single bamboo part diets and their potential implications by using 16S rRNA gene-based amplicon sequencing and metagenome shotgun sequencing. We found that the composition and function of the gut microbiome from captive giant pandas fed exclusively culms were significantly different from that of individuals fed shoots or leaves. During the culm feeding period, the gut microbiome showed strongest digestive capabilities for cellulose, hemicellulose and starch, and had the highest potential abilities for the biosynthesis of bile acids, fatty acids and amino acids. This suggests the microbiome aids in breaking down culm, which is more difficult for giant pandas to digest, as a means to compensate for the nutrient poor content of the culm. Genes related to fatty acid metabolism and tricarboxylic acid cycle enzymes were more abundant during the leaf stage diet than that in the shoot and culm stages. Thus, the microbiome may help giant pandas, which typically have low lipase levels, with fat digestion. These results illustrate that adaptive changes in the gut microbiome community and function may be an important mechanism to aid giant panda digestion when consuming different structural parts of bamboo.

Transcutaneous Auricular Vagus Nerve Stimulation: From Concept to Application - Yu Wang; Shao-Yuan Li; Dan Wang; Mo-Zheng Wu; Jia-Kai He; Jin-Ling Zhang; Bin Zhao; Li-Wei Hou; Jun-Ying Wang; Lei Wang; Yi-Fei Wang; Yue Zhang; et al. (Neuroscience Bulletin, 2021)

Effective identification of CRISPR/Cas9-induced and naturally occurred mutations in rice using a multiplex ligation-dependent probe amplification-based method - Sukumar Biswas; Rong Li; Jun Hong; Xiangxiang Zhao; Zheng Yuan; Dabing Zhang; Jianxin Shi (Theoretical and Applied Genetics, 2020)

Release from below- and aboveground natural enemies contributes to invasion success of a temperate invader - Yuan-Zheng Zhao; Ming-Chao Liu; Yu-Long Feng; Dong Wang; Wei-Wei Feng; Keith Clay; Lekeah A. Durden; Xiu-Rong Lu; Shuo Wang; Xiao-Lin Wei; De-Liang Kong (Plant and Soil, 2020)

Development of methods for effective identification of CRISPR/Cas9-induced indels in rice - Sukumar Biswas; Rong Li; Zheng Yuan; Dabing Zhang; Xiangxiang Zhao; Jianxin Shi (Plant Cell Reports, 2019)

Facile synthesis of Fe3O4@MOF-100(Fe) magnetic microspheres for the adsorption of diclofenac sodium in aqueous solution - Xiang Zheng; Jinlin Wang; Xiaolong Xue; Wanxia Liu; Yadong Kong; Rong Cheng; Donghai Yuan (Environmental Science and Pollution Research, 2018)

Joint Interpretation of Geological, Magnetic, AMT, and ERT Data for Mineral Exploration in the Northeast of Inner Mongolia, China - Gang Zhang; Qing-Tian Lü; Gui-Bin Zhang; Ping-Rong Lin; Zheng-Yuan Jia; Kui Suo (Pure and Applied Geophysics, 2018)

Lipid accumulation and anti-rotifer robustness of microalgal strains isolated from Eastern China - Cheng Yuan; Yan-Lin Zheng; Wan-Lu Zhang; Ru He; Yong Fan; Guang-Rong Hu; Fu-Li Li (Journal of Applied Phycology, 2017)

Different influences of field aging on nickel toxicity to Folsomia candida in two types of soil - Yu-Rong Liu; Jing Li; Ji-Zheng He; Yi-Bing Ma; Yuan-Ming Zheng (Environmental Science and Pollution Research, 2015)

Retraction Note to: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Response of bacterial pdo1, nah, and C12O genes to aged soil PAH pollution in a coke factory area - Xue-Mei Han; Yu-Rong Liu; Yuan-Ming Zheng; Xiao-Xia Zhang; Ji-Zheng He (Environmental Science and Pollution Research, 2014)

Analyzing and modeling rheological behavior of liver fibrosis in rats using shear viscoelastic moduli - Ying Zhu; Yi Zheng; Yuan-yuan Shen; Xin Chen; Xin-yu Zhang; Hao-ming Lin; Yan-rong Guo; Tian-fu Wang; Si-ping Chen (Journal of Zhejiang University-SCIENCE B, 2014)

Paludibacter jiangxiensis sp. nov., a strictly anaerobic, propionate-producing bacterium isolated from rice paddy field - Yan-Ling Qiu; Xiao-Zhu Kuang; Xiao-Shuang Shi; Xian-Zheng Yuan; Rong-Bo Guo (Archives of Microbiology, 2014)

Linkage between community diversity of sulfate-reducing microorganisms and methylmercury concentration in paddy soil - Yu-Rong Liu; Yuan-Ming Zheng; Li-Mei Zhang; Ji-Zheng He (Environmental Science and Pollution Research, 2014)

Effects of super absorbent polymers on soil microbial properties and Chinese cabbage (Brassica chinensis) growth - Xi Li; Ji-Zheng He; Yu-Rong Liu; Yuan-Ming Zheng (Journal of Soils and Sediments, 2013)

RETRACTED ARTICLE: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Structural determination of two new triterpenoid saponins acylated with monoterpenic acid from Gymnocladus chinensis Baill. - Wen Qi; Dan Yuan; Lian-Mei Yang; Ke-Hui Xie; Tian-Zhi Cai; Rong Yang; Hong-Zheng Fu (Natural Product Research, 2012)

Synthesis of aspirin eugenol ester and its biological activity - Jian-yong Li; Yuan-guang Yu; Qi-wen Wang; Ji-yu Zhang; Ya-jun Yang; Bing Li; Xu-zheng Zhou; Jian-rong Niu; Xiao-juan Wei; Xi-wang Liu; Zhi-qi Liu (Medicinal Chemistry Research, 2012)

Toxicity of profenofos to the springtail, Folsomia candida, and ammonia-oxidizers in two agricultural soils - Yu-Rong Liu; Yuan-Ming Zheng; Ji-Zheng He (Ecotoxicology, 2012)

Imprinting analysis of porcine MAGEL2 gene in two fetal stages and association analysis with carcass traits - Ling Guo; Mu Qiao; Chao Wang; Rong Zheng; Yuan-Zhu Xiong; Chang-Yan Deng (Molecular Biology Reports, 2012)

Single nucleotide polymorphism of CACNA2D1 gene and its association with milk somatic cell score in cattle - Zheng Rong Yuan; Jiao Li; Li Liu; Lu Pei Zhang; Li Min Zhang; Cui Chen; Xiao Jie Chen; Xue Gao; Jun Ya Li; Jin Bao Chen; Hui Jiang Gao; Shang Zhong Xu (Molecular Biology Reports, 2011)

Association of thyroglobulin gene variants with carcass and meat quality traits in beef cattle - Guan-Yu Hou; Zheng-Rong Yuan; Han-Lin Zhou; Lu-Pei Zhang; Jun-Ya Li; Xue Gao; Dong-Jing Wang; Hui-Jiang Gao; Shang-Zhong Xu (Molecular Biology Reports, 2011)

Molecular characterization and expression patterns of Lbx1 in porcine skeletal muscle - Zhe Chao; Jian Wu; Rong Zheng; Feng-E. Li; Yuan-Zhu Xiong; Chang-Yan Deng (Molecular Biology Reports, 2011)

Increased urinary 8-hydroxy-2′-deoxyguanosine levels in workers exposed to di-(2-ethylhexyl) phthalate in a waste plastic recycling site in China - Qian Wang; Li Wang; Xi Chen; Kai Min Rao; Shao You Lu; Sheng Tao Ma; Pu Jiang; Dan Zheng; Shun Qing Xu; Hong Yan Zheng; Jian Shu Wang; Zhi Qiang Yu; et al. (Environmental Science and Pollution Research, 2011)

Malignant transformation of 293 cells induced by ectopic expression of human Nanog - Yan-Li Lin; Zheng-Bin Han; Fu-Yin Xiong; Li-Yuan Tian; Xiao-Jie Wu; Shi-Wei Xue; Yan-Rong Zhou; Ji-Xian Deng; Hong-Xing Chen (Molecular and Cellular Biochemistry, 2011)

PpGalNacT2 participating in vanadium-induced HL-60 cell differentiation - Yuan Gao; You Bin Tu; Yi Guo; Ling Yan Yang; Xiang Hong Guo; Lan Xu; Zheng Rong Xu; Shi Liang Wu (Molecular Biology Reports, 2011)

Sequence Analysis of the Lactoferrin Gene and Variation of g.7605C→T in 10 Chinese Indigenous Goat Breeds - Jing-Fen Kang; Xiang-Long Li; Hui-Qin Zheng; Rong-Yan Zhou; Lan-Hui Li; Hong-Yuan Zhao (Biochemical Genetics, 2011)

Novel SNPs of the bovine CACNA2D1 gene and their association with carcass and meat quality traits - Zheng Rong Yuan; Shang Zhong Xu (Molecular Biology Reports, 2011)

A new hexenol glycoside from leaves of Smallanthus sonchifolius - Xiang Zheng; Gai Kuo; Dou De-Qiang; Chen Gui-Rong; Kang Ting-Guo; Shi Yu-Yuan; Li Xing-Tai; Dong Feng (Natural Product Research, 2010)

Genetic Polymorphisms of the CACNA2D1 Gene and Their Association with Carcass and Meat Quality Traits in Cattle - Guan-Yu Hou; Zheng-Rong Yuan; Xue Gao; Jun-Ya Li; Hui-Jiang Gao; Jin-Bao Chen; Shang-Zhong Xu (Biochemical Genetics, 2010)

Effects of mercury on the activity and community composition of soil ammonia oxidizers - Yu-Rong Liu; Yuan-Ming Zheng; Ju-Pei Shen; Li-Mei Zhang; Ji-Zheng He (Environmental Science and Pollution Research, 2010)

Molecular characterization, expression profile and association analysis with fat deposition traits of the porcine APOM gene - Gang Pan; Yayuan Fu; Bo Zuo; Zhuqing Ren; Dequan Xu; Minggang Lei; Rong Zheng; Yuan-Zhu Xiong (Molecular Biology Reports, 2010)

Association of MYF5 and MYOD1 Gene Polymorphisms and Meat Quality Traits in Large White × Meishan F2 Pig Populations - Min Liu; Jian Peng; De-Quan Xu; Rong Zheng; Feng-E Li; Jia-Lian Li; Bo Zuo; Ming-Gang Lei; Yuan-Zhu Xiong; Chang-Yan Deng; Si-Wen Jiang (Biochemical Genetics, 2008)

Microbial composition and diversity of an upland red soil under long-term fertilization treatments as revealed by culture-dependent and culture-independent approaches - Ji-Zheng He; Yong Zheng; Cheng-Rong Chen; Yuan-Qiu He; Li-Mei Zhang (Journal of Soils and Sediments, 2008)

Quantitative trait loci for carcass traits on pig chromosomes 4, 6, 7, 8 and 13 - Jing Hu Zhang; Yuan Zhu Xiong; Bo Zuo; Ming Gang Lei; Si Wen Jiang; Feng E Li; Rong Zheng; Jia Lian Li; Quan De Xu (Journal of Applied Genetics, 2007)

Assignment of CCR7 gene to chicken chromosome 27 by radiation hybrid panel mapping - Yong Tian; Li-zhi Lu; Yan Fu; Zheng-rong Tao; Jun-da Shen; De-qian Wang; Ai-ping Yuan; Zhao-zheng Yin (Journal of Zhejiang University-SCIENCE B, 2007)